Injury Prevention Strategies: Improving Strength and Flexibility for the Ankle : A Literature Review - Rini Wahyuni; Arsil; Gusril; Anton Komaini; Dally Rahman; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2023)
The importance of injury prevention in the world of sport, especially football, is increasingly recognized by health practitioners and coaches. This article aims to present an in-depth literature review on strategies for preventing ankle injuries in soccer athletes, with the main focus on increasing muscle strength and flexibility. The literature presented includes the latest research results, clinical guidelines, and empirical findings in an effort to increase ankle durability and stability. Literature analysis reveals that training programs aimed at strengthening the supporting muscles of the ankle, along with increasing flexibility, can reduce the risk of injury in soccer athletes. Additionally, this review explores effective post-injury rehabilitation methods to speed up the recovery process and prevent recurrence. Practical implications of this research include developing exercise programs tailored to individual needs, regular monitoring by medical staff, and educating athletes about the importance of prehabilitation treatment. The results of this literature review confirm that implementing an exercise program that focuses on increasing the strength and flexibility of the ankle supporting muscles is an effective strategy in preventing injuries and post-injury rehabilitation in soccer athletes. Conclusion Overall, muscle strengthening and increasing flexibility in the ankle is emerging as a significant approach in the prevention and management of injuries in soccer athletes, highlighting the crucial role of targeted training in improving their health and performance.